First trimester uterine artery Doppler, sFlt-1 and PlGF to predict preeclampsia in a high-risk population. (3rd July 2017) - Diguisto, Caroline; Piver, Eric; Gouge, Amélie Le; Eboue, Florence; Vaillant, Claudine Le; Maréchaud, Martine; Goua, Valérie; Giraudeau, Bruno; Perrotin, Franck
Abstract: Objective: The study aims to evaluate the accuracy of combining uterine artery Doppler (UAD), PlGF and sFlt-1 in the first trimester for preeclampsia screening. Methods: Prospectively enrolled women at high risk of preeclampsia were included. Transabdominal UAD measurements and serum biomarkers were collected between 11 and 13 weeks of gestation in three university hospitals and in one general hospital. The main outcome was preeclampsia. UAD parameters and biomarker levels among women with preeclampsia were compared with those of women in the unaffected group in univariate and multivariate analyses. Results: Out of 226 women included from May 2007 to January 2011, 27 (11.9%) women developed preeclampsia. Among women affected by preeclampsia, the lowest pulsatility index was higher ( p  = 0.02), bilateral notching was more frequent ( p  = 0.01), and PlGF was lower ( p  < 0.001). No significant differences were observed for other indicators. The multivariate model, adjusted for laboratory and sonographic indicators, had an area under the curve (AUC) estimated at 0.76, which was not significantly different from the AUC of the univariate model adjusted only for PlGF ( p  = 0.7). Conclusion: In a high-risk population, PlGF in the first trimester is useful for predicting preeclampsia, but neither sFlt-1 nor any UAD indices improved the prediction of preeclampsia.